Evaluation of the Families, Attitudes toward Environment Pollution - qassim, Wissam; abed, rajaa (Iraqi National Journal of Nursing Specialties, 2014)
Objectives: To evaluate the families’ attitudes toward environment pollution, and determine the relationshipbetween families’ attitudes towards environment pollution and their demographic characteristics of age,education, type of family, and socioeconomic status.Methodology: A descriptive design is carried throughout the present study to evaluate families’ attitudes towardenvironment pollution for the period of October 5th2013 to May 7th2014. A non-probability "purposive" sample of(110) families’ is selected. The sample is comprised of two groups; (75) urban families’ and (35) rural ones. Anevaluation tool is designed and constructed for the purpose of the study. It is consisted of (4) main parts;demographic data, attitudes toward environment pollution, attitudes toward producing factors for houseenvironment pollution, and method of house environment arrangement. Content validity and internal consistencyreliability are determined for the study instrument through a pilot study. Data are collected through the use of thestudy instrument and structured interview as means of data collection. Data are analyzed through the applicationof descriptive data analysis approach, which includes frequency, percent and mean of scores.Results: The results of the study indicate that the vast majority of families’ has experienced high level of attitudestoward environment pollution, producing factors for house environment pollution, and method of houseenvironment arrangement.Recommendations: The study recommends that education program by mass media can be forwarded to families’with regard to issues related to environment pollution in order to increase their awareness, improves theirattitudes, and positively change their behaviors